Atlantic Bottlenose Dolphins (Tursiops truncatus) as A Sentinel for Exposure to Mercury in Humans: Closing the Loop - Reif, John S. (Vet Sci, 2015)
Mercury (Hg) is a ubiquitous global contaminant with important public health implications. Mercury is released from a variety of anthropogenic, industrial processes, enters the earth's atmosphere and is re-deposited onto the earth’s surface in rainfall. Much of this Hg enters the oceans which cover the majority of the earth’s surface. In the marine environment, inorganic Hg is converted to the most toxic form of the element, methylmercury, and biomagnified through the trophic levels of the food web. The bottlenose dolphin (Tursiops truncatus) is the apex predator in many estuarine and coastal ecosystems. Due to their long life span and trophic position, bottlenose dolphins bioaccumulate high concentrations of contaminants including Hg, thus making them an important sentinel species for ecosystem and public health. Bottlenose dolphins in Florida bioaccumulate high concentrations of Hg in their blood, skin and internal organs. The concentrations of Hg in blood and skin of bottlenose dolphins of the Indian River Lagoon, FL (IRL) are among the highest reported world-wide. In previous studies, we demonstrated associations between concentrations of total Hg in the blood and skin of IRL dolphins and markers of endocrine, renal, hepatic, hematologic and immune system dysfunction. The predominant manifestation of exposure to mercury in humans is neurotoxicity. During the 1950s and 1960s, residents of Minamata bay, Japan were exposed to high concentrations of methyl mercury as the result of ingestion of fish and shellfish that had become contaminated in this infamous environmental disaster. Affected adults had severe motor and sensory abnormalities often leading to death. Methyl mercury crosses the placenta during pregnancy. Children exposed in utero were born with multiple congenital anomalies and also suffered from neurologic disorders. Significantly, local cats that consumed Hg contaminated fish developed severe signs of neurotoxicity which led to their subsequent description as the “dancing cats of Minamata bay”. Unfortunately, the cause of these strange manifestations in cats was not recognized in time to prevent hundreds of additional cases from occurring. More recent studies have shown that exposure to mercury as a result of seafood consumption during pregnancy may result in multiple cognitive and neurodevelopmental effects in children. The levels of mercury found in bottlenose dolphins and the health effects we identified alerted us to the possibility of an important public health hazard. The IRL occupies 40 percent of the east coast of Florida and is bordered by counties with approximately 2.5 million human inhabitants. Therefore, we hypothesized that local inhabitants in communities bordering the IRL could be at risk of exposure to Hg from the consumption of fish and shellfish. We measured hair Hg in 135 local residents and found a mean concentration of 1.53 µg/g which was higher than that from previous studies of sport fishermen and coastal residents in other states. Over 50% of participants had a hair Hg concentration which exceeded the U.S. EPA exposure guideline. Hair Hg concentration was directly related to the frequency of seafood consumption and to the proportion of fish and shellfish obtained from local recreational sources. This study clearly exemplifies the importance of an animal sentinel in identifying a public health hazard and is virtually unique in “closing the loop” between animal and human health.